Do Consumers’ Attitudes Towards Food Technologies and Motives of Food Choice Influence Willingness to Eat Cereal Products Fortified with Fibre? - Jeżewska-Zychowicz Marzena; Królak Maria (Polish Journal of Food and Nutrition Sciences)
The aim was to assess the relationships between willingness to eat cereal products fortified with fibre, attitudes towards food technologies and some food choice motives.